Main factors that influenced the increase in inflation in Colombia, in the years 2015 and 2016 (2022)
The present work tries to show the behavior of the inflation indexes in Colombia during the years 2010 to 2019 with a main focus in the years 2015 and 2016, period in which the highest levels of inflation in the country will be selected, analyzing the elements and factors that have influenced its increase or decrease and the positive or negative results caused by this economic phenomenon. The analysis contains a series of data on inflation and the Consumer Price Index IPC, obtained from the Bank of the Republic and from the National Administrative Department of Statistics DANE, which are reflected in different graphs, which allow a descriptive analysis of the variation of inflation in Colombia in the last decade, annual variation, monthly variation of the years where the highest rates were presented in the general increase in prices, variation by type of expenditure and main cities. Finally, we will see the actions implemented by the Bank of the Republic, the regulatory body, to keep inflation rates within the limit range, through monetary policy which aims to maintain a low and stable inflation rate and reach the maximum sustainable level of product and employment